Bologne et Naples au prisme des biens communs : pluralité et exemplarité de projets de gestion « commune » de l’urbain - Simone Ranocchiari; Christophe Mager (Développement Durable et Territoires)
The urban policies of many Italian cities have been imbued with the concept of “common goods”. Two modalities aimed at framing autonomous initiatives of citizens involved in the management and production of the urban will be studied : the “regulations for the shared management of urban commons goods”, promoted by the association Labsus in about 150 cities, including Bologna ; the framework set up by the public authorities of Naples, instituting a regulation of the commons, different, at least in part, from the practices inspired by Labsus. From the presentation of these policies, this article develops a critical approach to the concept of “common good”, arguing the need to think about common as a political principle rather than as an object.